A new angle on Middle Stone Age hunting technology in South Africa - Mohapi, Moleboheng (My University, 2009)
Lithic points have always been assumed to have been spears and they occur in Middle Stone Age (MSA) assemblages in great numbers before the Howiesons Poort. They disappear or occur only very rarely in the Howiesons Poort Industry (when segments appear to replace them). After the Howiesons Poort, points become common again. Segments, which are part of some Later Stone Age (LSA), as well as MSA assemblages, have, like points, been associated with hunting weapons. This study reports on the results of a technological analysis of South African points and segments. The points come from two MSA sites in KwaZulu-Natal: Sibudu Cave and Umhlatuzana Rock Shelter. MSA segments are from the Howiesons Poort assemblages of Sibudu and Umhlatuzana, while LSA segments are from Jubilee Shelter in the Magaliesberg. Changing hunting strategies are examined through time by investigating the changing technologies used for points and segments. This is a new contribution because no-one has ever used the same methodology to compare segments and points. Sibudu and Umhlatuzana points cover a long span of time. Sibudu points come from layers that have optically stimulated luminescence ages of between ~73,000 – ~35,000 years ago and they include specimens from the Still Bay up to the final MSA. Radiocarbon ages from Umhlatuzana may be unreliable because they are likely to be minimum ages and because of rotational slippage of some of the sediments. MSA segments from Sibudu have an age of approximately 70,000 – 60,000 years ago while LSA segments from Jubilee have an age of about 6,000 years ago. There is overwhelming evidence that points from Sibudu and Umhlatuzana were used as hafted spearheads. Results of morphometric analyses, tip cross-sectional area (TCSA) and tip penetrating angles support Marlize Lombard’s suggestion (based on use-trace analyses) that post-Howiesons Poort points from Sibudu were used as hafted hand-held spears while Still Bay points served several purposes which included hunting. Similar results were obtained from the analysis of Umhlatuzana points. Changes in the use of points over time are not as evident at Umhlatuzana as at Sibudu, but the morphologies of their bases suggest that final MSA points iii were hafted differently from points in the older MSA phases. Rock types appear not to have played any role in the form and function of points from the two sites. Sibudu and Umhlatuzana segments are likely to have been used to tip different types of hunting weapons. Their size attributes, TCSA and tip penetrating angles are within the range of attributes of other MSA segments (from other South African contexts), some of which have been suggested to have been used as hunting weapons. When hafted vertically, transversely or diagonally, they are likely to have been used as arrowheads and when hafted in pairs (back-toback), they could have been used as darts, or even spearheads in the case of large segments. Results of the Sibudu and Umhlatuzana technological analyses of segments confirm results of residue analysis and experimental work. These indicate that segments could have been hafted in various configurations, but that they were used mainly to tip hunting weapons. Jubilee Shelter LSA segments are, however, probably too small to have been used effectively as hunting tools (especially if hafted vertically and diagonally) and micro-wear analysis by Wadley and Binneman suggests that they were used as compound parts of knives rather than as projectiles. Rock types seem to have played an important role in the form and function of segments at Sibudu because segments form three populations based on rock types. The small quartz tools might have been hafted transversely while larger, elongated hornfels and dolerite segments might have been hafted diagonally or back-to-back. Rock types seem not to have influenced the forms and functions of Umhlatuzana and Jubilee Shelter segments. Jubilee segments (LSA) are as equally un-standardized as Sibudu and Umhlatuzana segments (MSA). There is, however, some standardization amongst the length/breadth ratios of Howiesons Poort quartz segments from Sibudu.